2020
DOI: 10.1371/journal.pntd.0008229
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the molecular detection of Sarcoptes scabiei from a skin scraping in patients with suspected scabies

Abstract: Scabies is a highly contagious parasitic disease associated with long-term residence in nursing homes, and it is a public health burden worldwide. However, atypical skin manifestations are frequent and the widely used diagnostic test based on microscopic examinations has limited sensitivity. We evaluated the diagnostic value of polymerase chain reaction (PCR) from skin scraping in patients with suspected scabies. Adult patients with suspected scabies, unrelated diseases or healthy volunteers were enrolled at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…For many years, it has been believed that the S. scabiei transmission could occur between host species and that their descent with new genetic variability could infect new animal species (Fain, 1994; Fraser et al ., 2017). In recent decades, molecular studies have attempted to better explain the epidemiology of S. scabiei in different host species (Amer et al ., 2014; Fraser et al ., 2017, 2019; Peltier et al ., 2017; Bae et al ., 2020). These studies demonstrated the existence of various genotypes analysing different molecular markers, as the cox1 gene, suggesting some host–parasite adaptation for S. scabiei , as supported by this study.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, it has been believed that the S. scabiei transmission could occur between host species and that their descent with new genetic variability could infect new animal species (Fain, 1994; Fraser et al ., 2017). In recent decades, molecular studies have attempted to better explain the epidemiology of S. scabiei in different host species (Amer et al ., 2014; Fraser et al ., 2017, 2019; Peltier et al ., 2017; Bae et al ., 2020). These studies demonstrated the existence of various genotypes analysing different molecular markers, as the cox1 gene, suggesting some host–parasite adaptation for S. scabiei , as supported by this study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 ] Molecular test has shown different sensitivities in various studies, ranging from 37.9% to 86%. [ 10 11 12 ] Although PCR might increase positivity, since it is costly, it is mostly suggested in pool sampling where an outbreak is suspected. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ]. Moreover, it has been utilized to detect S. scabiei from the skin scrapings of suspected scabies patients [ 27 ]. Compared with microscopic and immunological examinations, PCR displays more advantages in terms of sensitivity and specificity, and multiplexed PCR can detect several parasite-specific sequences in the same reaction.…”
Section: Conventional Diagnostic Methods For Medical Parasite and Arthropodmentioning
confidence: 99%